Verbal instructions override the meaning of facial expressions - Bublatzky, Florian; Guerra, Pedro; Alpers, Georg W. (Scientific reports, 2018)
Psychological research has long acknowledged that facial expressions can implicitly trigger affective psychophysiological responses. However, whether verbal information can alter the meaning of facial emotions and corresponding response patterns has not been tested. This study examined emotional facial expressions as cues for instructed threat-of-shock or safety, with a focus on defensive responding. In addition, reversal instructions were introduced to test the impact of explicit safety instructions on fear extinction. Forty participants were instructed that they would receive unpleasant electric shocks, for instance, when viewing happy but not angry faces. In a second block, instructions were reversed (e.g., now angry faces cued shock). Happy, neutral, and angry faces were repeatedly presented, and auditory startle probes were delivered in half of the trials. The defensive startle reflex was potentiated for threat compared to safety cues. Importantly, this effect occurred regardless of whether threat was cued by happy or angry expressions. Although the typical pattern of response habituation was observed, defense activation to newly instructed threat cues remained significantly enhanced in the second part of the experiment, and it was more pronounced in more socially anxious participants. Thus, anxious individuals did not exhibit more pronounced defense activation compared to less anxious participants, but their defense activation was more persistent.
Gesehen am 02.04.2020